(untitled) (KYAMC Journal, 2025)
The COVID-19 pandemic posed unprecedented challenges to global health systems, leading to the urgent development and deployment of vaccines to mitigate the spread of the virus and reduce morbidity and mortality. Vaccination programs were instrumental in controlling the pandemic, but they also sparked discussions about potential adverse events, particularly those related to autoimmune disorders. Vitiligo is a chronic autoimmune skin condition characterized by the destruction of melanocytes, resulting in the loss of skin pigmentation. While the exact etiology of vitiligo remained unclear, it is believed to involve a complex interplay of genetic, environmental, and immunological factors. Emerging reports raised questions about the potential association between COVID-19 vaccination and the onset or exacerbation of autoimmune conditions like vitiligo. This led to growing interest in understanding whether COVID-19 vaccines, which elicited robust immune responses, could potentially trigger or worsen vitiligo in predisposed individuals. Addressing these concerns was critical to ensuring vaccine confidence and providing comprehensive guidance to patients, particularly those with pre-existing autoimmune conditions or a family history of vitiligo. This article aimed to explore the relationship between COVID-19 vaccination and vitiligo, examining the evidence available at the time and its implications for clinical practice.